Project-Based Learning Approach in Teaching Semantics: The Creation of Arabic Thematic Dictionaries - Suci Ramadhanti Febriani; Tafiati Tafiati; Prayoga Saputra; Desriwela Ade Mela (Indonesian Journal of Arabic Studies, 2025)
Purpose – This study aims to identify and analyze the implementation of project-based learning in teaching semantics through the creation of Arabic thematic dictionaries at UIN Imam Bonjol Padang. The research seeks to explore how this method contributes to enhancing students’ vocabulary mastery, creativity, and contextual understanding of Arabic. Design/methods/approach – Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving fifth-semester Arabic literature students. The data were analyzed using Miles and Huberman’s interactive model, which includes data collection, reduction, presentation, and conclusion drawing. Findings – The findings reveal that creating thematic dictionaries using a project-based learning model improves students’ semantic understanding, vocabulary acquisition, and creative thinking. Learners were able to construct meaning contextually, apply the theory of semantic fields, and demonstrate increased engagement and motivation. The project also fostered collaborative learning, critical thinking, and better learning outcomes, as evidenced by improved average scores post-intervention. Research implications – This study supports project-based learning as an effective pedagogical model in Arabic language instruction, particularly for semantic development. It offers practical insights for educators in higher education to integrate meaningful, contextual tasks that foster both linguistic and cognitive skills. Further research is recommended to quantitatively examine the broader impact of this model